Nazarabad, a Role Model Industrial Town in Iran (A Case Study) - Akbari, Mohammad Rahim (International Journal of Bio-resource and Stress Management, 2023)
During recent decade, rural industrialization has been noticed through socio-economic developments in Iran. The study is aimed at understanding the impact of social and economic aspects based on descriptive analytic method. There have been chosen 240 families as sample from 1962 local families using kukran formula. Based on the above statistics, Nazarabad industrial towns has experienced a positive promotion playing major role in job opportunities, rural products marketing, gender balances, public awareness, public communication ultimately reducing migration from rural to bigger towns and cities.